Isolation and identification of common fungal spp. from commercial broiler feeds available in market of Sylhet District, Bangladesh - Islam, MT; Hossain, MK; Elahi, ATMM; Purkayastha, M; Rahman, MM (International Journal of Natural Sciences, 2016)
The present study was designed to investigate the mycological contamination of commercial broiler feeds used in poultry establishments in sylhet, Bangladesh. The feed samples of commercial broiler feed (Starter, Grower and Finisher) were collected from the different areas of Sylhet district. A total of 189 commercial broiler feed samples where 63 Starter, 63 Grower and 63 Finisher were collected from the different areas of local market in Sylhet. The selected areas were Kadamtali, Shibjong, Khadim, Kamal Bazar, Dakshin Surma, Fenchugonj. From the feed samples analyzed for the presence of fungal agents, 144 (76.2%) were found positive for one or more fungal species. Fungal isolates were found among 36 (57%) of the 63 Starter feed samples, 45 (71.4%) of the 63 Grower feed samples and 63 (100%) of the 63 Finisher feed samples. The fungal agents isolated from Broiler Starter Feeds, Aspergillus spp. 51 (70.8%) has the highest frequency of occurrence, followed by Fuserium spp. 12 (16.7%) and least is Rhizopus sp. 9(12.5%). Similarly, in case of Broiler Grower Feeds, Aspergillus spp. 66 (68.8%) has the highest frequency of occurrence, followed by Fuserium spp. 18 (18.7%) and least is Rhizopus sp. 12(12.5%). In case of Broiler Finisher Feeds, Aspergillus spp. 90 (69.8%) has the highest rate of occurrence followed by Fuserium spp. 24 (18.6%) and least is Rhizopus sp. 15 (11.6%) respectively. International Journal of Natural Sciences (2014), 4(2) 38-41